KEMAMPUAN MENULIS TEKS PROSEDUR KOMPLEKS SISWA KELAS X SMA DHARMA LOKA PEKABARU - Hidayat, Alkahfi; ', Auzar; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study titled Writing Ability Complex Text Procedure Class X SMA Dharma Loka Pekabaru. This study aims to determine the level of writing ability and the structure of the text linguistic element complex procedure of class X SMA Dharma Loka Pekanbaru. The method used is descriptive analysis method with quantitative approach. Data of this study is the result of the test's ability to write text complex procedure given in class X SMA Dharma Loka Pekanbaru and consists of five classes, with a population of 143 and the number of samples 106. The results ability to write text on a complex procedure of getting structural aspects average value 83.302 average with a high category and the ability to write text on a complex procedure aspects of linguistic elements to get the average value of 81.92 with the high category.Key Words: Writing skills, text complex procedures, student class x sma dharma loka pekabaru